Japanese Application of Bioassays for Environmental Management - Takashi Kusui (The Scientific World Journal)
The increasing number of existing and new chemicals demands ecotoxicological data as well as toxicological data for pre- and postmarketing risk assessments. Although human health has been the major concern in Japanese environmental management, ecosystem health is becoming the big issue as the need for preserving the diversity of ecosystems has been recognized. This recognition is changing the regulatory framework in Japan, resulting in new actions toward establishment of water-quality standards for aquatic organisms and ecotoxicological assessment of existing chemicals. At the same time, the need to assess complex liquids that contain several kinds of chemicals is increasing. The ecotoxicological study of Japanese effluents shows that the present chemical-specific standards are not enough to protect aquatic ecosystems. These two factors encourage the application of ecotoxicological tests as well as the toxicological data.